Industrialización de Leguminosas, Lenteja (lens culinaris) y Garbanzo (cicer arietinum), Venoga - García Acurio, Jhonatan Guillermo (2017)
The following investigation was aimed to elaborate a vegetal product (sausage) based on lentil (Lens culinaris) and chickpea (Cicer arietinum), focused on the industrialization of these legumes which are aimed at the population that has a vegetarian lifestyle or vegan, athletes or those who are headed for a healthy life. The research was carried out in the Laboratory of Investigation of the Meat Industry of Agroindustrial Engineering Career. The vegetable product was made from lentil and chickpea, which were used in greater proportion in the formulation in order to be the meat substitute; the combination of legumes and cereals provides the essential amino acids for proper nutrition so it was necessary to incorporate wheat flour and soy protein. On the other hand, in order to obtain a homogeneous paste, the use of cassava starch and carrageenan was chosen due to its binder function. For its flavoring, cumin, garlic, onion, salt and pepper powder were used, thus allowing the taste of the original product to be maintained. "VENOGA" was subjected to a sensorial analysis to obtain the best treatment by means of a completely randomized block design with factorial arrangement of (3x2), it was verified that the best treatment was t_3 with a concentration of 50% of lentil, 50% of chickpea and at a blanching temperature of 80 ° C x 15 min. These are the ideal variables to obtain a product with characteristics similar to a common sausage. According to the nutritional analysis performed in LABOLAB, the vegetable product of 500 g of sample tube the following percentages 64.02% of humidity, 11.84% of protein, 0.41% of fat, 3.01% of ash, 0 , 02% fiber, 0.00% sugar, 20.70% total carbohydrate, 188.72% sodium, 0.00% cholesterol and 0.48% sodium chloride. The microbiological analysis of the best treatment indicates that the plant product is within the limits established by the INEN 1338 standard being a suitable product for consumption. The yield of raw materials, inputs, condiments and additives was 149.34%, due to the gain of weight when incorporating water in the “cuteriado” process. Talking about the cost of the best treatment was worth $ 1.88 PVP in a presentation of 500 g that was obtained, reaching to the conclusion that the product in addition to being healthy is affordable with the pric, for people who are fed differently.